The mental health issues of eunuchs in the context of social exclusion - Syeda Farhana Kazmi; Rubina Bibi; Tahir Pervaiz; Rabia Bashir (Journal of the Pakistan Medical Association, 2020)
Objective: To study the mental health problems in eunuchs, the neglected segment that has been facing social exclusion and exploitation on behalf of social layers of the society. Method: The study was conducted from Jan 2017 to April 2017and adopted a qualitative approach by engaging eight eunuchs’ group purposefully through focused group discussion to unearth the issues related to eunuchs in Hazara Division, The participants were properly informed about the purpose of the study and their consent was conferred. The discussion was recorded in local language and their views have been transcribed and analyzed by comparative statements for drawing results through coding of the target groups. Results: The severe kind of economic and social pressures of poverty and social neglect resulted depression, anxiety and suicidal tendencies are found among this group, affecting overall mental health among such neglected gender group, due to the fact that eunuchs have not been provided with basic social rights. In addition, there is no love and care provided by the kin and relatives resulting in the eunuchs facing psychological complications in daily life. Conclusion: As an outcome, the eunuchs face psychological complications in daily life. The condition necessitates encouragement and social acceptance of eunuch for a normal and healthy life in the society. Furthermore socio-psychosocial aid through regular counselling for creation of hope for leading a normal life. Keywords: Mental health, Social exclusion, Psychological distress. Continuous...